(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses information about the city of Bukhara, the main city of Central Asia, of researchers of the 20th century. In this case, after Bukhara city became an object of scientific research, we will see that its studies have developed considerably. Basically, we can see that the contribution of O.A Sukhareva, M.S.Andreyev in the historical researches of Bukhara city is incomparable. In addition, we can witness that information about the city of Bukhara was studied with the help of representatives of the diplomatic mission, orientalists, qualified officials, and military personnel. Ignatiev, the representative of the diplomatic mission, also covered the stories of the Russian soldiers. At the same time, the scientific activities of Khanikov, Leman, Zavyalov and other researchers were analyzed.